2016
DOI: 10.1039/c6mb00235h
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence for the role of a site of the di-iron catalytic center of ferritins in tuning the kinetics of Fe(ii) oxidation

Abstract: Ferritin is a nanocage protein made of 24 subunits. Its major role is to manage intracellular concentrations of free Fe(ii) and Fe(iii) ions, which is pivotal for iron homeostasis across all domains of life. This function of the protein is regulated by a conserved di-iron catalytic center and has been the subject of extensive studies over the past 50 years. Yet, it has not been fully understood how Fe(ii) is oxidized in the di-iron catalytic center and it is not known why eukaryotic and microbial ferritins oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…1B), and conformational changes in amino acid residues of sites C and B have been observed 19. Moreover, consistent with this speculation is our previous Mössbauer study of PfFtn, in which we found that the Mössbauer parameters of Fe(II) in site C before the addition of dioxygen are different than those after the addition of dioxygen (Table 1) 10. The importance of site C for efficient catalysis of Fe(II) oxidation has been reported for other ferritins namely Escherichia coli ferritin A 25, 26 and Desulfovibrio vulgaris Hildenborough ferritin 27.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…1B), and conformational changes in amino acid residues of sites C and B have been observed 19. Moreover, consistent with this speculation is our previous Mössbauer study of PfFtn, in which we found that the Mössbauer parameters of Fe(II) in site C before the addition of dioxygen are different than those after the addition of dioxygen (Table 1) 10. The importance of site C for efficient catalysis of Fe(II) oxidation has been reported for other ferritins namely Escherichia coli ferritin A 25, 26 and Desulfovibrio vulgaris Hildenborough ferritin 27.…”
Section: Discussionsupporting
confidence: 86%
“…Before the addition of dioxygen to ferritin containing 48 Fe(II) per ferritin 24‐mer, the percentages of 57 Fe(II) in sites A, B, and C were 41%, 40%, and 19%, respectively (Table 1). According to the distribution model we explained previously 10 it could be concluded that in 32% of the subunits (~ 7 subunits per 24‐mer) sites A, B, and C were occupied with Fe(II) (A II B II C II subunits). After 0.7 s all the Fe(II) in sites A and B was converted to the peroxodiferric species but the Fe(II) in site C was not oxidized (Table 1).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations